2012
DOI: 10.1037/a0026021
|View full text |Cite
|
Sign up to set email alerts
|

Do nice guys—and gals—really finish last? The joint effects of sex and agreeableness on income.

Abstract: Sex and agreeableness were hypothesized to affect income, such that women and agreeable individuals were hypothesized to earn less than men and less agreeable individuals. Because agreeable men disconfirm (and disagreeable men confirm) conventional gender roles, agreeableness was expected to be more negatively related to income for men (i.e., the pay gap between agreeable men and agreeable women would be smaller than the gap between disagreeable men and disagreeable women). The hypotheses were supported across… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
157
4
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 179 publications
(179 citation statements)
references
References 113 publications
(145 reference statements)
16
157
4
2
Order By: Relevance
“…In particular, these studies have shown that low agreeableness and high openness are associated with higher income. In addition, previous studies have indicated that the negative association between agreeableness and income, in particular, is curvilinear-that is, the agreeableness-income relationship is steeper at lower levels of agreeableness (Judge et al 2012). Gender also seems to play an important role in the personality-income relationship.…”
Section: Personality and Important Life Outcomesmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, these studies have shown that low agreeableness and high openness are associated with higher income. In addition, previous studies have indicated that the negative association between agreeableness and income, in particular, is curvilinear-that is, the agreeableness-income relationship is steeper at lower levels of agreeableness (Judge et al 2012). Gender also seems to play an important role in the personality-income relationship.…”
Section: Personality and Important Life Outcomesmentioning
confidence: 99%
“…Recent studies based on large Anglo-American and British samples have provided initial evidence that income is related to an individual's personality (e.g., Judge et al 2012;Heineck 2014;Mueller and Plug 2006). In particular, these studies have shown that low agreeableness and high openness are associated with higher income.…”
Section: Personality and Important Life Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…In non-human species, exploratory or bold behavior may increases risk of predation (guppies: Dugatkin, 1992;Godin & Davis, 1995;theoretical model: Wolf, van Doorn, Leimar, & Weissing, 2007; for review, see Smith & Blumstein, 2008), and among humans, extraversion can similarly carry fitness-relevant costs -extraverts are disproportionately represented in hospitals with injury or illness (Nettle, 2005) and their pronounced sensation-seeking can lead to traumatic injury (Field & O'Keefe, 2004) and legal trouble (Ellis, 1987). Similarly, high levels of agreeableness can carry fitness costs; individuals who avoid conflict are less desirable as mates in a variety of species, including humans (e.g., fighting fish: Doutrelant & McGregor, 2000;Midas cichlid: Barlow, 1986;humans: Lukaszewski & Roney, 2011), and high agreeableness may lead individuals to forgo their own objectives and risk social exploitation (Judge, Livingston, & Hurst, 2011). Although high levels of neuroticism may cognitively and affectively motivate an individual to protect limited social opportunities, high neuroticism is associated with impaired somatic health (Cohen & Williamson, 1991;Glaser & Kiecolt-Glaser, 2005;Herbert & Cohen, 1993;O'Leary, 1990) and can place burdensome strain on social relationships (e.g., Buss, 1991a;Neeleman, Sytema, & Wadsworth, 2002).…”
Section: The Benefits and Costs Of Personality Traitsmentioning
confidence: 99%
“…69 These findings hint at a 68 For a definition of each trait, see Mueller and Plug (2006). 69 See also Judge, Livingston, and Hurst (2012). One must, of course, be cautious in basing conclusions about the contribution of gender differences in individual regression coefficients (on either categorical or continuous double bind for women.…”
mentioning
confidence: 99%